Understanding drivers, barriers and information sources for public participation in marine citizen science - Martin, Vicki; Christidis, Les; Lloyd, David; Pecl, Gretta (Journal of science communication, 2016)
Interviews were conducted with 110 marine users to elicit their salient beliefs about recording marine species in a citizen science project. The results showed that many interviewees believe participation would increase knowledge (either scientific, the community's, or their own). While almost half of the interviewees saw no negative outcomes, a small number expressed concerns about targeting of marine species by others, or restrictions on public access to marine sites. Most of the people surveyed (n = 106) emphasised the importance of well-designed technological interfaces to assist their data collection, without which they would be unlikely to engage in the project.